POTENSI KONSORSIUM Bacillus spp. DAN Pseudomonas fluorescens UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA TANAMAN CABAI RAWIT - Nensi Agustina; Arika Purnawati; Endang Triwahyu Prasetyawati (Plumula : Berkala Ilmiah Agroteknologi, 2022)
Cayenne pepper (Capsicum frutescens L.) is one of the horticultural crops with high economic value. The production of cayenne pepper is often constrained by stem wilt disease caused by the fungus Fusarium sp. This research aims to know the effect of the consortium of Bacillus spp. and Pseudomonas fluorescens as biological agents to control fusarium wilt in cayenne pepper. This research was conducted at the screenhouse of UPN "Veteran" East Java. The research began in January 2021 until April 2021. The study was arranged using a Split Plot Design with two factors, namely antagonistic bacteria and application time and was repeated 4 times. The first factor is antagonistic bacteria with 5 levels of treatment, namely without the provision of antagonistic bacteria, Bacillus spp. isolate code Ba9, Bacillus spp. isolate code Ba17, P. fluorescens, Bacillus spp. isolate code Ba9 + P. fluorescens, Bacillus spp. isolate code Ba17 + P. fluorescens. The second factor is the application time with 2 levels of treatment, namely before transplanting seedlings and after transplanting seedlings. If it is known that there is a significant effect of the treatment, then the Duncan Multiple Range Test (DMRT) is carried out at the 5% level. The treatment of the consortium of Bacillus spp. isolate code Ba9 and P. fluorescens caused a delay in the incubation period of Fusarium sp. by 23.42%, increasing plant height by 20.55%, and accelerating the emergence of prospective flowers, while the treatment with the consortium of Bacillus spp. isolate code Ba17 and P. fluorescens suppressed the intensity of fusarium wilt disease by 29.03%, increasing the number of leaves by 56.58% compared to the single aplication of bacteria.